Uporaba pravičnosti v mednarodnih sodnih sporih - Zbičajnik, Sebastjan (Pravnik, 2013)
Justice has been and still is the subject of much discussion both in modern as well as in ancient times, especially in relation to philosophy and theology. Indeed, since the start of recording, justice has been formulated into the written word and understanding, notwithstanding the requirements of individuals and society as a whole. Through history and progress, justice has been continuously put into practice and formalized. Justice has so often been the underlying asset for law and order, and this was also the reason why laws were aimed at achieving justice, and consequently used for the implementation of legal values. This is why from a historical perspective, legal thought has evolved through positivistic and natural attitudes. Legal positivism has largely avoided ideas of justice and other legal and philosophical issues, whereas the natural approach to law was closer to the idea of fairness even in the international context. This research into justice in the international legal proceedings demonstrates the broad dimension of the concept and its impact on the development of international law. The fact is that justice is a potential source of decisionmaking in the international legal sphere.
Keywords: mednarodna sodišča; pravičnost; sodni postopek; spori